The Impact Agility Training Toward Dribbling Abilty of Futsal Beginners Player - Setiawan, Heru; Tangkudung, James; Puspitorini, Wahyuningtyas; Syarif, Algifari (Department of Physical Education, Sport, Health and Recreation, 2020)
Futsal is a popular game for all people in the world. It needed agility technique to drib the ball. The purpose of study was to find the effect of agility training on dribbling ability for futsal beginner player. The study used quantitative approach using experimental one group. The study gave the treatment for futsal beginner. It did in futsal club Bengkulu. The data was taken from the agility test in dribbling playing (pre-test and post-test). The technique of data analysis used t-test paired two sample for means. The result of finding shows that the average of pretest score obtained a score of 11.95, while average of posttest obtained a score of 16.05. Furthermore, the statistical analysis of the T-Test obtained t-count of -11.56 < t-table = 2.1009. From these results it can be concluded that there is the effect of agility training toward dribbling ability in futsal playing.